GAMBARAN TINGKAT KECEMASAN DAN PERILAKU PROTOKOL KESEHATAN PADA PENYINTAS COVID-19 - Frida Anindita Yulianti (2022)
The government has made regulations or efforts to overcome the spread of COVID-19, such as, 3M to 5M, implementing PSBB, PPKM and lockdown. However, until now the Covid-19 cases have not disappeared, some have even been exposed to it twice. The long-term impact of this virus disrupts the mental health of Covid-19 survivors, making survivors feel afraid, anxious and anxious. The purpose of this study was to describe the level of anxiety and behavior of the health protocol on covid 19 survivors in Kampung Bojong RW 005. In this study, the researcher used a sampling technique, namely random sampling, which means it is a technique that has similarities with simple random sampling with a sample of 94 respondents. This study used a behavioral health and anxiety protocol questionnaire. Of the 94 samples, 97 respondents with a percentage of 92.4% had good knowledge, 86 respondents with a percentage of 81.9% had a good attitude, 87 respondents with a percentage of 82.9% had good actions and as many as 65 respondents with a percentage of 61.9% had moderate anxiety. The results of this study are, an overview of the health behavior of covid-19 survivors, there are 97 respondents (92.4%) with good knowledge, as many as 86 respondents (81.9%) have a good attitude and as many as 97 respondents (92.4%). have good actions. An overview of the anxiety of COVID-19 survivors, there are 56 (61.9%) respondents have moderate anxiety and the remaining 36 (38.1%) respondents have low anxiety. It is hoped that health cadres can provide education about the importance of health protocol behavior so that the impact during the COVID-19 pandemic can be minimized. Keywords: Anxiety, Health Protocol Behavior, Survivors, Pandemic